Acclimation to water stress improves tolerance to heat and freezing in a common alpine grass - Sumner, Emma E.; Williamson, Virginia G.; Gleadow, Roslyn M.; Wevill, Tricia; Venn, Susanna E. (Oecologia, 2022)
Alpine plants in Australia are increasingly exposed to more frequent drought and heatwaves, with significant consequences for physiological stress responses. Acclimation is a critical feature that allows plants to improve tolerance to environmental extremes by directly altering their physiology or morphology. Yet it is unclear how plant performance, tolerance, and recovery are affected when heat and water stress co-occur, and whether prior exposure affects responses to subsequent climate extremes. We grew a common alpine grass species under high or low watering treatments for three weeks before exposure to either none, one, or two heat stress events. We determined photosynthetic heat and freezing tolerance (LT 50 , mean temperature causing 50% irreversible damage to photosystem II) and growth. Physiological adjustments to low watering, including more negative water potentials and reduced growth, were also characterised by improved tolerance to high and low-temperature extremes. Shifts to higher heat tolerance were also evident with increasing exposure to heat stress events, though freezing tolerance was not affected. Acclimation effects were mostly short-term, however; prior exposure to heat and/or water stress had little to no effect on growth and thermal tolerance following the six-week recovery period. We conclude that rapid acclimation to water and heat stress that co-occur during summer enhances the capacity of alpine plants to tolerate increasingly frequent temperature extremes.